2021
DOI: 10.1111/cas.15070
|View full text |Cite
|
Sign up to set email alerts
|

Differences in treatment and survival between elderly patients with thoracic esophageal cancer in metropolitan areas and other areas

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In our study, it was found that the 5‐year survival rate of elderly patients with EC stage I was 53.4%, and the median survival time was 64 months while the 5‐year survival rate of EC stage IV was 26.5%, and the median survival time was 22 months. In our study, the 3‐year OS rate was 71.7% among Stage I patients, highly similar to 71.6% in metropolitan areas in Japan, which implies the importance for the detection and timely treatment for EC 28 . TNM staging of EC is a general comprehensive judgment of the stage in the development of EC, which integrates three indicators (Tumor size, lymph node, metastasis) that have an important impact on the prognosis of EC patients, so it is an important factor affecting the treatment and prognosis of patients with EC 5,29 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our study, it was found that the 5‐year survival rate of elderly patients with EC stage I was 53.4%, and the median survival time was 64 months while the 5‐year survival rate of EC stage IV was 26.5%, and the median survival time was 22 months. In our study, the 3‐year OS rate was 71.7% among Stage I patients, highly similar to 71.6% in metropolitan areas in Japan, which implies the importance for the detection and timely treatment for EC 28 . TNM staging of EC is a general comprehensive judgment of the stage in the development of EC, which integrates three indicators (Tumor size, lymph node, metastasis) that have an important impact on the prognosis of EC patients, so it is an important factor affecting the treatment and prognosis of patients with EC 5,29 .…”
Section: Discussionsupporting
confidence: 71%
“…In our study, the 3-year OS rate was 71.7% among Stage I patients, highly similar to 71.6% in metropolitan areas in Japan, which implies the importance for the detection and timely treatment for EC. 28 TNM staging of EC is a general comprehensive judgment of the stage in the development of EC, which integrates three indicators (Tumor size, lymph node, metastasis) that have an important impact on the prognosis of EC patients, so it is an important factor affecting the treatment and prognosis of patients with EC. 5,29 The earlier the tumor stage is, the higher the surgical resection rate will be, the better the treatment effect will be.…”
Section: Discussionmentioning
confidence: 99%
“…Increased age at diagnosis and an increasing life expectancy of the population in Western countries pose a problem for the treatment of esophageal cancer in the elderly, as treatment choices are governed by comorbidities, patient performance status and patient priorities (3,4). In many landmark trials defining the role of chemoradiation in esophageal cancer, older patients have been underrepresented or excluded, making extrapolation of trial data to the elderly population problematic (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This should be a more accurate reflection of the effect of age on patients' outcome, compared with analyzing age in ranges. As in previous studies 23 , 24 , the log-rank test was used to determine the prognostic value of age with better accuracy. Furthermore, multivariate Cox regression analysis was performed to eliminate non-significant explanatory variables 6 , 16 , 25 and validate the independent prognostic value of age.…”
Section: Discussionmentioning
confidence: 99%